Effect of Valipora campylancristrota (Cestoda, Cryporinchidae) on growth parameters of silver carp (Hypophthalmichtys molitrix) - Honcharov, S. L.; Soroka, N. M.; Dubovyi, A. I.; Semenko, O. V.; Pryima, O. B.; Svarchevskyi, O. A.; Sobolta, A. H.; Tafiichuk, R. I. (Regulatory Mechanisms in Biosystems, 2024)
In order to determine the impact of Valipora campylancristrota Wedl, 1855 (Cestoda, Cryporinchidae) plerocercoids on growth, development, and condition factors of juvenile silver carp (Hypophthalmichthys molitrix Valenciennes, 1844) (age category 0+), two experimental groups of fish were established and maintained under identical conditions in a pond farm. The first group of silver carp was spontaneously infected with the larvae of the causative agent of valiporosis, while the second group of fish was free from this invasion. Results indicated that in April, weight and length of the infected silver carp were 23.5% and 4.4% lower, compared to the healthy fish, and the Fulton’s condition factor in the diseased fish was 8.4% lower compared to the non-infected silver carp. When conducting this research in October, it was determined that the weight, length, and condition factor of the silver carp in the first group were 32.0%, 10.3%, and 35.6% lower, respectively, compared to the fish in the second group that were free from cestode larvae. Clinical examination revealed emaciation, reduced muscle mass in the caudal and anal fin regions of the examined fish. Some individuals with valiporosis exhibited spinal deformities and asymmetrical abdominal cavities due to intestinal distension. Post-mortem examinations revealed a distended gallbladder filled with bile, indicative of acute and chronic catarrhal inflammation of the gallbladder mucosa. Qualitative changes in bile were observed: in silver carp infected with valiporosis, the bile was a yellowish-green color and more viscous.